Extracellular Proteome Analysis and Flavor Formation During Soy Sauce Fermentation - Zhao, Guozhong; Ding, Li-Li; Yao, Yunping; Cao, Yanping; Pan, Zhi-Hui; Kong, De-Hua (Frontiers in Microbiology, 2018)
Aspergillus oryzae is an excellent strain for soy sauce fermentation because of the complicated enzyme system especially protease. The aim of this study was to investigate the key enzymes and flavors during soy sauce fermentation. A comparative assessment of the extracellular enzymes during different fermentation stages at the proteomic level using iTRAQ analysis was presented. Lots of important enzymes which are related to amino acid and glucose metabolisms were still participating in the material decomposition under high-salt stress. Dipeptidase, dipeptidyl aminopeptidase, leucine aminopeptidase, aspartic protease pep1 and extracellular metalloproteinase played a positive role during the early stage of soybean mash fermentation, whereas leucine aminopeptidase A and extracellular metalloproteinase NpI were the dominant proteolytic enzymes during the later period of fermentation. Simultaneously, β-glucosidase and β–xylanase made great effects in glucose metabolism during the whole process of fermentation. The results showed that protease and amylolytic enzymes were complementary to the formation of flavors such as alcohols, acids, esters, aldehydes, furans and pyrazines during soy sauce fermentation.